Trois exemples du personnage feminin dans le roman francophone d’Afrique subsaharenne: salimata, perpetue et laokole - Drame, Siacka (Kansas State University, 2012)
Francophone Literature from Sub-Saharan Africa is an important indicator of the extent of the awakening by African people to their realities that link them to the past and the present. Novels of prominence written from the sixties to the nineties demonstrate how well their authors appreciate the characteristics of their societies. In this respect, some African writers such as Mongo Beti, Regina Yaou and Emmanuel Dongala in their respective works The Suns of Independence by Ahmadou Kourouma, Perpétua and the Habit of Unhappiness by Mongo Beti, and Johnny Mad Dog by Emmanuel Dongala offer very different characters, but with the same basic function of showing the African readers how poorly women have been treated in the past and today, and that without improving women's plight couldn't fulfill its role of protection, or nurturing towards its members. I will talk first about the submissive woman. Second, I will focus on the willingness of woman. Third, women in African society and then I will focus on Perpetua and the female characters in Perpetua and the Habit of Unhappiness by Mongo Beti. At the end of my study, I would lay the emphasis on the character of Laokole in Johnny Mad Dog.
Keywords: African literature; African Literature (0316)